2017
DOI: 10.1186/s40643-017-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of membrane fatty acids and proteins of Shewanella putrefaciens treated with cinnamon oil and gamma irradiation

Abstract: Background:In order to detect the antimicrobial mechanism of combined treatment of cinnamon oil and gamma irradiation (GI), the membrane fatty acids and proteins characteristics of Shewanella putrefaciens (S. putrefaciens) treated with cinnamon oil and GI, and the distribution of cinnamon oil in S. putrefaciens were observed in this study. Results:The membrane lipid profile of S. putrefaciens was notably damaged by treatments of cinnamon oil and the combination of cinnamon oil and GI, with significantly fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…aureus, Shewanella putrifaciens, and C. albicans treated with different EOs and EO-ACs. ,,, Such pore formation results in the damage of cell membrane and consequent efflux of intracellular contents including K + ions, nucleotides/DNA/RNA, and protein (Figures B–D and ; panel D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus, Shewanella putrifaciens, and C. albicans treated with different EOs and EO-ACs. ,,, Such pore formation results in the damage of cell membrane and consequent efflux of intracellular contents including K + ions, nucleotides/DNA/RNA, and protein (Figures B–D and ; panel D).…”
Section: Discussionmentioning
confidence: 99%
“…33 The above findings corroborated with previous studies on planktonic forms of Listeria monocytogenes , Pseudomonas fluorescens , S. aureus , Shewanella putrifaciens , and C. albicans treated with different EOs and EO-ACs. 23,35,37,38 Such pore formation results in the damage of cell membrane and consequent efflux of intracellular contents including K + ions, nucleotides/DNA/RNA, and protein (Figures 6B–D and 9; panel D).…”
Section: Discussionmentioning
confidence: 99%
“…The LS has also been used in combination with bioactive molecules in food, such as nisin, reuterin, and Laminaria [40,41]. An antimicrobial effect has also been shown with cinnamon EO acting synergistically with other methods, for example, with gamma irradiation [42] or nisin [43].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobicity of EOs and/or their components enables the hydrophobic molecules to preferentially reside in the lipids of the cell membrane and mitochondria, disrupting the structure and rendering cell permeability to be compromised, eventually leading to the leakage of cellular contents [20]. Emerging evidence has revealed that EO antimicrobial activities are attributed to the incorporation of exogenous fatty acids (the EOs) in altering the cell membrane's phospholipid profile [12,38,39]. While phospholipids are the common membrane constituents found in bacteria, plants and mammals, this commonality, however, raises concerns that this particular EO mechanism may be rendered unspecific, as EOs could also exert the same type of toxic effects on any biological membranes.…”
Section: Toxicity Of Eos and Components On The Biological Membranesmentioning
confidence: 99%